MANAJEMEN PEMBELAJARAN BERBASIS PENDEKATAN PERUBAHAN PERILAKU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DI SMP NEGERI 3 PADEMAWU PAMEKASAN - Dr. Ali Nurhadi, M.Pd.; Dedi Yusup (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2019)
Management in learning must be programmed according to the approach to behavior change in order to increase student motivation. This was done at SMP Negeri 3 Pademawu Pamekasan. This research approach is qualitative with the type of case study research. The results of the first study planning a behavioral change approach in increasing student motivation in Pademawu Pamekasan Middle School 3, including: 1) Teachers use the PAKEM learning model. 2) Implement a system of approaches, giving motivation, uswah or examples and spiritual support, rules in the form of 5S and school order; 3) Application of the rules and regulations of the institutions that get positive responses from students. The second is the application of the behavior change approach in increasing student motivation in Pademawu Pamekasan Middle School 3, including: 1) The teacher provides motivation for students such as order notes and uswah or examples. 2) The teacher uses the PAKEM learning model; and 3) Teachers apply reward and praise strategies for students who excel in both the academic and non-academic fields. These three factors support the behavior change approach in increasing student motivation in Pademawu State Yunior School 3 in increasing student motivation in Pademawu State Pamekasan Yunior School, including: 1) active students in the classroom; 2) The existence of a mosque is also an existing library. While the inhibiting factors, including: 1) If the teacher is too close to students, the student will lower the teacher and students who are naughty will talk more and more without being noticed by students; b) Not all teachers apply the behavior change approach.